Innovative Work Behavior Lecturers: A Bibliometric Approach in Higher Education Research - Neng Siska Fitriani (Journal of Psychological Insight, 2025)
Innovative Work Behavior (IWB) among lecturers has become increasingly important in responding to rapid changes in higher education systems and academic demands. This study aims to map and analyze the development of research on lecturers’ use of IWBs and to identify dominant themes and influencing factors within the existing literature. The study examines scholarly publications focusing on lecturers in higher education using a bibliometric approach. Data were retrieved from major scientific databases and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, and author collaboration networks. The results show a gradual increase in IWB-related publications, with research clusters primarily focusing on organizational support, leadership, motivation, and academic innovation. However, the overall volume of studies remains limited and fragmented. This study contributes by providing a comprehensive bibliometric overview of lecturers’ IWB research, highlighting research gaps and emerging themes. The findings offer practical implications for higher education institutions to design policies and interventions that foster innovative behavior among lecturers and guide future empirical studies.